If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y = 3x + -19 Reorder the terms: 5y = -19 + 3x Solving 5y = -19 + 3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '5'. y = -3.8 + 0.6x Simplifying y = -3.8 + 0.6x
| -2+13=14x-5-13x | | 3b-4/3 | | 3x=65.14 | | 3z+2z+z=3z+25+2 | | 6bc^2-28bc+16b=0 | | 3x+4ab=4x-5ab | | 5(2n+6)=-4(-5-2n)+3n | | 4(3x-7)=9(2x-5) | | (3/2)x-2=19 | | 12x^2-6/-4=0 | | x+35=35 | | -14-(-11)=x/11 | | 3x+10=2x+6 | | 5x-4=6x+9 | | 20+a=2a+10 | | 4y-7=2y-38 | | 2n^3-18n^2-14n=0 | | 6ds^2-28ds+16d=0 | | 3/5x-1/10x-5 | | Log(b)64=2 | | 14j+j+4j+j-18j=14 | | c^2-3*c-10= | | (5-3x)(2x-7)=0 | | 26=11.6+y | | 7p-2p=15 | | 25v=-125 | | 2w-w=11 | | 13c-3c=20 | | n-(-7)=26 | | 3(5x-5)=25.5 | | 8g-5g=18 | | 6x-2y=-36 |